Numerical investigation for the calculation of TiO2-water nanofluids' pressure drop in plain and enhanced pipes - Celen, Ali; Kayaci, Nurullah; Cebi, Alican; Demir, Hakan; Dalkilic, Ahmet Selim; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
In this investigation, a numerical model having two-dimensional equations was obtained by a CFD program and authors' experimental data were evaluated for the verification procedure of the numerical outputs. The experimental case study includes the single-phase flow of pure water in plain and micro-fin pipes whereas the numerical one has the simulated results of TiO2 particles suspended in single phase water flow in equivalent pipes at a constant heat flux. Hydrodynamics and thermal behaviors of the water-TiO2 flow were calculated by constant heat flux and temperature-dependent settings. Physical specifications of nanofluids were calculated by means of the results of authors' previous ANN analyses. This study illustrates local and average values of temperature, pressure, and velocity distributions in the tested pipes; furthermore, comparisons of pressure drop characteristics are given in terms of nanoparticle concentrations and tube types. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Pressure drop; Nanofluid; Single-phase flow; CFD; ANN; HEAT-TRANSFER ENHANCEMENT; THERMAL-CONDUCTIVITY; AL2O3-WATER NANOFLUIDS; FORCED-CONVECTION; VISCOSITY; AL2O3; WATER; TIO2; Thermodynamics; Mechanics